2012
DOI: 10.3382/ps.2012-02268
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella collected from nest run cart shelves in commercial shell egg processing facilities

Abstract: Salmonella, a member of the bacterial family Enterobacteriaceae, may be recovered from foods and processing facilities. High levels of Enterobacteriaceae in the processing plant environment can be an indication of inadequate sanitation. This experiment was designed to determine if nest run egg carts serve as reservoirs for Salmonella. Eggs that are produced by hens not housed in buildings connected to the processing plant are referred to as nest run. Many of these eggs are transported to a central processing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Adesiyun et al (1) used pulse-field gel electrophoresis to determine the relationships among Salmonella Enteritidis isolates recovered from each of the Caribbean countries studied. Salmonella serotypes differ among layer farms and countries (9,28,29,34), and all serotypes recovered in the present study have been documented previously in the Caribbean region (1,10,20).…”
Section: Trinidad and Tobago Grenada St Lucia ----------------------mentioning
confidence: 60%
“…Adesiyun et al (1) used pulse-field gel electrophoresis to determine the relationships among Salmonella Enteritidis isolates recovered from each of the Caribbean countries studied. Salmonella serotypes differ among layer farms and countries (9,28,29,34), and all serotypes recovered in the present study have been documented previously in the Caribbean region (1,10,20).…”
Section: Trinidad and Tobago Grenada St Lucia ----------------------mentioning
confidence: 60%
“…Overall, the authors found that aerobic plate counts (APC) of eggs obtained from the in‐line type of facility were higher in comparison to those obtained from the off‐line one. Also, Musgrove and others () determined the possibility of nest run egg carts to act as reservoir of Salmonella , with comparisons between an off‐line facility and a mixed‐operation one (with in‐line processed eggs and supplementation with off‐line ones). It appears that Salmonella prevalence in the off‐line facility (12%) was significantly different ( P < 0.001) from the mixed‐operations one (36%).…”
Section: Preharvest Methods For Reducing the Risk Of Salmonella Contamentioning
confidence: 99%
“…Usually this happens without any lesions and furthermore, when egg storage conditions allow it, this foodborne pathogen may be isolated from the shell egg, as it survives in the forming egg (Gast and others ; Gantois and others ; Raspoet and others ; Howard and others ). Transmission of this serotype may happen either vertically (Gast and Beard ; Galàn 2001; Groisman ; Gast and others ; Gast and others ; Gyles and others ; Gast and others ; Ibarra and Steele‐Mortimer ; Li and others ; Mastroeni and others ; Dawoud and others ; De Vylder and others ; Desin and others ; Linke and Goldman ; Shah and others ; Howard and others ; Kumar ) or horizontally (Holt ; Holt and others ; Jones and others ; Davies and Breslin ; De Reu and others ; Musgrove and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Risk of Salmonella external contamination of eggs during egg processing does still exist in the U.S. and other developed countries. In-line egg processing facilities where the egg processing facilities are physically connected to the egg layer operation, off-line operations where they are not physically connected, and mixed-line operations that include a combination of in-line processing as well as externally shipped in eggs have been shown in several studies to be a source of Salmonella contamination with or without egg washing [76][77][78]. In addition, numerous opportunities for general microbial cross contamination occur in these types of operations as the eggs move through the processing facilities [79,80].…”
Section: Postharvest Contamination Routesmentioning
confidence: 99%
“…In addition, numerous opportunities for general microbial cross contamination occur in these types of operations as the eggs move through the processing facilities [79,80]. In a series of studies on mixed-line and offline egg processing facilities, Musgrove and coworkers [78,81] demonstrated that metal carts with unpainted plywood shelves, commonly referred to as nest run carts could serve as sources of microbial cross contamination.…”
Section: Postharvest Contamination Routesmentioning
confidence: 99%